The effectiveness of non-operative treatment in high-grade liver and spleen injury in children - KIYAN, GÜRSU; KARADENİZ CERİT, KIVILCIM; ERGELEN, RABİA (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2018)
BACKGROUND: Although a nonoperative treatment approach is preferred for blunt liver and spleen trauma in childhood, there are significant differences between clinics in the algorithms used. The approach to high-grade liver and spleen injury is still controversial, particularly as grade V liver and spleen injuries are not included in the American Pediatric Surgical Association guideline. The aim of this study was to present experience with a non-operative treatment approach to children with high-grade liver and spleen injuries. METHODS: Pediatric patients who were referred to Marmara University Hospital's emergency department between January 2012 and January 2017 due to liver and spleen injury related to blunt abdominal trauma and who were followed up in the clinic were included in the study. The data were analyzed retrospectively in terms of age, sex, type of trauma, degree of organ damage, accompanying organ damage, duration of intensive care unit (ICU) and hospital stay, need for transfusion, and treatment method (operative-nonoperative). Grade I, II, or III organ damage was classified as low-grade, while grade IV and V organ lesions were classified as high-grade. RESULTS: Of 2800 patients who were diagnosed by radiological imaging with liver and spleen injuries due to blunt abdominal trauma and hospitalized in the clinic, 88 were included in the study. Isolated liver injury was determined in 41 patients, while 39 had an isolated spleen injury, and 8 had injuries to both organs. An accompanying organ injury was observed in 30 (34%) patients. In all, 83 (94%) patients underwent non-operative treatment and a surgical approach was required for 5 patients (6%). Patients with high-grade liver injury had a significantly longer period of hospitalization, duration of ICU stay, and greater transfusion requirement, compared with patients with low-grade liver injury (p=0.001, 0.001, and <0.001, respectively). A surgical approach was more common among patients with a high-grade liver injury than for patients with a low-grade injury (p=0.045). There was no significant difference between patients with a high- or low-grade spleen injury in terms of age, sex, duration of hospitalization, duration of ICU stay, transfusion requirement, or accompanying organ injury (p=0.254, 0.739, 0.114, 0.135, 0.057, 0.721, respectively). Similarly, there was no significant difference in terms of non-surgical or surgical treatment approach between the patients with high-grade spleen injury and those with low-grade spleen injury (p=0.488). CONCLUSION: Non-operative treatment is a feasible treatment method in pediatric patients with a high-grade blunt liver or spleen injury. Nonetheless, pediatric surgeons should bear in mind that patients with high-grade liver damage may require more surgical treatment.
Keywords: Blunt abdominal trauma; liver injury; non-operative management; pediatric trauma; spleen injury; ABBREVIATED BEDREST PROTOCOL; EVIDENCE-BASED GUIDELINES; BLUNT SPLEEN; PROSPECTIVE VALIDATION; MANAGEMENT